Analysis of the Mediating Role of OCB in the Relationship Between LOC, Self-Efficacy, and Organizational Justice on Employee Performance - Nursanti, Tia; Darmawan, Akhmad; Arofah, Rifka Utami; Suyoto, Suyoto; Haryanto, Totok (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of LOC, self-efficacy, and organizational justice on employee performance with OCB as a mediating variable among employees in the cutting department of PT. Hyup Sung Indonesia. This study uses quantitative research with saturated sampling or census method. The population consists of 132 employees in the cutting department. Data were collected using direct questionnaires. Data analysis used SEM-PLS. The results show that LOC does not significantly affect employee performance, but has a positive and significant effect on OCB. Self-efficacy and organizational justice positively and significantly affect employee performance and OCB. OCB positively and significantly affects employee performance and mediates the effects of self-efficacy and organizational justice on employee performance, but does not mediate the effects of LOC. The analysis results show that organizational justice is the most influential variable in improving employee performance, both directly and through the mediating role of OCB. This study contributes to strengthening human resource studies through the role of OCB in improving performance. The findings of this study also provide guidelines for organizations in improving fairness practices to encourage positive work behavior.